Adverse Event Rates Change Favorably Over Time for Patients Bridged With the HeartWare Left Ventricular Assist Device. Issue 6 (November 2017) - Maltais, Simon; Aaronson, Keith D.; Teuteberg, Jeffrey J.; Slaughter, Mark S.; Najjar, Samer S.; Jeevanandam, Valluvan; Pham, Duc T.; McGee, Edwin C.; Leadley, Katrin; Kormos, Robert L.
Abstract : The HeartWare Ventricular Assist System (HVAD) provides significant improvements in survival and quality of life, and here, we seek to evaluate temporal differences in the adverse event (AE) rates. Patients (n = 382) in the ADVANCE bridge-to-transplant and continued access protocol trial were assessed for bleeding, cardiac arrhythmia, infection, ischemic and hemorrhagic stroke, and right heart failure during predetermined time periods (⩽30, >30–180, >180–365, >365–730, >730–1, 095 days) after HVAD implant. The Kaplan–Meier survival at 30 days, 6 months, 1, 2, and 3 years was 98%, 90%, 84%, 71%, and 63%, respectively. There were significantly fewer total AEs in days >30–180 (events per patient year [EPPY] = 5.34) compared with the first 30 days post HVAD implantation (EPPY = 30.36; p < 0.0001). The total AE rate in days >180–365 (EPPY = 4.09) was also significantly lower than the event rate in days >30–180 (EPPY = 5.34; p < 0.0001). Incidence of cardiac arrhythmias, infections, strokes, and right heart failure were highest immediately post implant and lower rates occurred after 6 months. After 1 year, all AEs exhibited stable rates that were comparable up to 3 years of support (all p > 0.05). This changing risk over time has clinically meaningful implications toward improving patient management.